Comparison of NiS2 and α-NiS hollow spheres for supercapacitors, non-enzymatic glucose sensors and water treatment. Issue 39 (17th September 2015) - Wei, Chengzhen; Cheng, Cheng; Cheng, Yanyan; Wang, Yan; Xu, Yazhou; Du, Weimin; Pang, Huan
Abstract : NiS2 and α-NiS hollow spheres are prepared via a template-free method. When NiS2 and α-NiS hollow spheres were evaluated for supercapacitors, glucose sensors and water treatment, it was found that the hollow α-NiS spheres exhibited better performance than the NiS2 . Abstract : NiS2 hollow spheres are successfully prepared by a one-step template free method. Meanwhile, α-NiS hollow spheres can also be synthesized via the calcination of the pre-obtained NiS2 hollow spheres at 400 °C for 1 h in air. The electrochemical performances of the as-prepared NiS2 and α-NiS hollow sphere products are evaluated. When used for supercapacitors, compared with NiS2 hollow spheres, the α-NiS hollow sphere electrode shows a large specific capacitance of 717.3 F g −1 at 0.6 A g −1 and a good cycle life. Furthermore, NiS2 and α-NiS hollow spheres are successfully applied to fabricate non-enzymatic glucose sensors. In particular, the α-NiS hollow spheres exhibit good catalytic activity for the oxidation of glucose, a fast amperometric response time of less than 5 s, and the detection limit is estimated to be 0.08 μM. More importantly, compared with other normally co-existing interfering species, such as ascorbic acid, uric acid and dopamine, the electrode modified with α-NiS hollow spheres shows good selectivity. Moreover, the α-NiS hollow spheres also present good capacity to remove Congo red organic pollutants from wastewater by their surface adsorption ability.